Structure Elucidation and Biosynthesis of Orobanchol - Wakabayashi, Takatoshi; Ueno, Kotomi; Sugimoto, Yukihiro (Frontiers in Plant Science, 2022)
Strigolactones (SLs), a class of phytohormones that regulate diverse developmental processes, were initially characterized as host-derived germination stimulants for seeds belonging to the genera Striga, Orobanche, and Phelipanche. Orobanchol (1), which is detected in the root exudates of several plants and recognized as a prevalent SL, was first isolated from the root exudates of red clover as a germination stimulant for Orobanche minor in 1998. However, the structure of this stimulant proposed at that time was disputable considering its predicted germination-inducing activity for Striga gesnerioides. The genuine structure of orobanchol was elucidated following a decade-long controversy, which ultimately facilitated the understanding of the importance of SL stereochemistry in Striga seed germination. Recently, studies focusing on clarifying the biosynthesis pathway of orobanchol are being conducted. Cytochrome P450 monooxygenases are involved in orobanchol biosynthesis downstream of carlactonoic acid (CLA) via two pathways: either through 4-deoxyorobanchol or direct conversion from CLA. Substantial progress in the identification of more SL structures and clarification of their biosynthetic mechanisms will further contribute in the comprehension of their structural diversity’s functional importance and agricultural applications. Herein, we have reviewed the history leading to the discovery of the genuine structure of orobanchol and the current understanding of its biosynthetic mechanisms.